Penegakan dan Perlindungan Hukum Terhadap Korban Kejahatan Seksual Maupun Pemerasan Pada Aplikasi Online Dating - Elvira Zikra; Tantimin (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2022)
The Covid-19 pandemic that has spread around the world has severely restricted all kinds of community activities, thus demanding the rapid development of internet network technology. The disease also has an impact on the frequency of sexual violence against children and adolescents that occurs on online dating apps. It is not enough to handle matters under the provisions of Law No. 11 of 2008 on Information and Electronic Transactions as amended by Law No. 19 of 2016 on Amendments to Law No. 11 of 2008 on Information and Electronic Transactions (hereinafter referred to as the ITE Act) and/or Law No. 44 of 2008 on Pornography (hereinafter referred to as the Pornography Act). The aim of the study was to find a legal framework and protection that better helps victims of sex crimes and extortion on online dating apps. The legal research methods used in this article are doctrinal (dogmatic). The strategy includes looking at law enforcement arrangements and legal protections for victims of sex crimes and extortion through online dating apps, with the aim of increasing criminal law knowledge. The findings of this study reveal that various kinds of law enforcement in Indonesia still lack a victim-centered view, both in terms of regulation and victim protection, and victims have not received justice. It even shows that existing rules have traits that can be used to contradict good morality. However, misuse of programs that may contain elements of decency, such as cyber sex, continues to raise legal concerns.